2019
DOI: 10.1016/j.cjca.2018.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in HIV

Abstract: Stroke is a heterogeneous disease in persons living with HIV (PLWH). HIV is thought to increase the risk of stroke through both HIV-related and traditional stroke risk factors, which vary with respect to the patient's age and clinical characteristics. Numerous studies show that detectable viremia and immunosuppression increase the risk of stroke across all ages while traditional risk factors are more common in the aging HIV population. As PLWH age and acquire traditional stroke risk factors, the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 80 publications
0
44
0
6
Order By: Relevance
“…A systematic review done by Addallah et al 37 reported that this could be due to HIV-associated opportunistic infections, HIV-induced coagulopathy, and chronic inflammatory processes that can accelerate atherosclerosis. Another systematic review by Bogorodskaya et al 38 also reported that some antiretrovirals (lopinavir, indinavir, and abacavir) were also associated with an increased risk of stroke.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review done by Addallah et al 37 reported that this could be due to HIV-associated opportunistic infections, HIV-induced coagulopathy, and chronic inflammatory processes that can accelerate atherosclerosis. Another systematic review by Bogorodskaya et al 38 also reported that some antiretrovirals (lopinavir, indinavir, and abacavir) were also associated with an increased risk of stroke.…”
Section: Discussionmentioning
confidence: 97%
“…It was believed that the elevated incidence of stroke in HIV infected patients was caused by the increased prevalence of opportunistic infections and inflammation due to immunosuppression, and older ART regimens that predisposed patients to dyslipidemia and lipodystrophy [ 11 ]. However, ART also contributes to the risk of stroke, both directly by accelerating atherosclerosis and indirectly by increasing life expectancy [ 10 ].…”
Section: Factors Contributing To the Development Of Stroke In Hivmentioning
confidence: 99%
“…Stroke is an abrupt interruption of constant blood supply to the brain, causing permanent or partial loss of brain function. Several clinical and postmortem studies have documented the association between HIV infection and the risk of stroke [ 6 , 10 , 11 , 12 , 13 , 14 ]. The number of stroke hospitalizations in the HIV infected population has dramatically increased in recent years, despite an overall decline in the number of stroke hospitalizations alone [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation into the aetiology of stroke in patients younger than 45 years found that in Africa, stroke in this group is usually associated with Human Immunodeficiency Virus (HIV) infection (Singer et al, 2013). This risk for stroke in individuals living with HIV is increased both by the condition and the antiretroviral therapy (ART) used to treat the condition (Bogorodskaya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%